Mitochondrial apoptosis is dispensable for NLRP3 inflammasome activation but non‐apoptotic caspase‐8 is required for inflammasome priming. (2nd July 2014) - Allam, Ramanjaneyulu; Lawlor, Kate E; Yu, Eric Chi‐Wang; Mildenhall, Alison L; Moujalled, Donia M; Lewis, Rowena S; Ke, Francine; Mason, Kylie D; White, Michael J; Stacey, Katryn J; Strasser, Andreas; O'Reilly, Lorraine A; et al.
Abstract: A current paradigm proposes that mitochondrial damage is a critical determinant of NLRP3 inflammasome activation. Here, we genetically assess whether mitochondrial signalling represents a unified mechanism to explain how NLRP3 is activated by divergent stimuli. Neither co‐deletion of the essential executioners of mitochondrial apoptosis BAK and BAX, nor removal of the mitochondrial permeability transition pore component cyclophilin D, nor loss of the mitophagy regulator Parkin, nor deficiency in MAVS affects NLRP3 inflammasome function. In contrast, caspase‐8, a caspase essential for death‐receptor‐mediated apoptosis, is required for efficient Toll‐like‐receptor‐induced inflammasome priming and cytokine production. Collectively, these results demonstrate that mitochondrial apoptosis is not required for NLRP3 activation, and highlight an important non‐apoptotic role for caspase‐8 in regulating inflammasome activation and pro‐inflammatory cytokine levels. Synopsis: Mitochondria are believed to have an important role in NLRP3 activation. Using 14 strains of knockout mice, this study finds no evidence for the involvement of mitochondrial damage in NLRP3 function, but shows that caspase‐8 is needed for inflammasome priming. The essential mitochondrial apoptosis executioners, BAX and BAK are not required for NLRP3 activation. Genetic deletion of the mitochondrial permeability transition pore component cyclophilin D, the mitochondrial anti‐viral signalling protein (MAVS) or the mitophagy regulator Parkin does not impact on NLRP3 activity. Caspase‐8 expression is required for efficient inflammasome priming and Toll‐like‐receptor‐induced cytokine production. Abstract : Mitochondria are believed to have an important role in NLRP3 activation. Using 14 strains of knockout mice, this study finds no evidence for the involvement of mitochondrial damage in NLRP3 function, but shows that caspase‐8 is needed for inflammasome priming.